Characterisation of a putative oxidoreductase in Escherichia coli: YdgJ - Cusin, Lola M.L. (2020)
Antibiotic resistance is one of the main challenges faced by humanity in the 21st century. In 2016, the Bolt lab identified by a genetic screen an uncharacterised putative oxidoreductase called YdgJ that conferred resistance to the antibiotic nalidixic acid in Escherichia coli. This protein was isolated and purified for in vitro study, and further genetic analysis of YdgJ was carried out in parallel. The genetic analysis revealed that the YdgJ gene did not convey nalidixic resistance, contrary to earlier experiments. Surprisingly, expression of YdgJ protein caused increased sensitivity to ROS. We predicted that YdgJ would bind to cofactor NAD(P), but this could not be confirmed experimentally. We gained evidence that the YdgJ protein formed a trimeric structure, in agreement with predictions from bioinformatics. Overall, the mechanism of action of YdgJ could not be uncovered, but several clues hinted towards a role in ROS detoxification or cell metabolism. Further experiments will be required to reach a full understanding of the YdgJ gene and its associated product.